Gaining more from doing less? The effects of a one-week deload period during supervised resistance training on muscular adaptations - Max Coleman; Ryan Burke; Francesca Augustin; Alec Piñero; Jaime Maldonado; James P. Fisher; Michael Israetel; Patroklos Androulakis Korakakis; Paul Swinton; Douglas Oberlin; Brad J. Schoenfeld (PeerJ, 2024)
Background Based on emerging evidence that brief periods of cessation from resistance training (RT) may re-sensitize muscle to anabolic stimuli, we aimed to investigate the effects of a 1-week deload interval at the midpoint of a 9-week RT program on muscular adaptations in resistance-trained individuals. Methods Thirty-nine young men (n = 29) and women (n = 10) were randomly assigned to 1 of 2 experimental, parallel groups: An experimental group that abstained from RT for 1 week at the midpoint of a 9-week, high-volume RT program (DELOAD) or a traditional training group that performed the same RT program continuously over the study period (TRAD). The lower body routines were directly supervised by the research staff while upper body training was carried out in an unsupervised fashion. Muscle growth outcomes included assessments of muscle thickness along proximal, mid and distal regions of the middle and lateral quadriceps femoris as well as the mid-region of the triceps surae. Adaptions in lower body isometric and dynamic strength, local muscular endurance of the quadriceps, and lower body muscle power were also assessed. Results Results indicated no appreciable differences in increases of lower body muscle size, local endurance, and power between groups. Alternatively, TRAD showed greater improvements in both isometric and dynamic lower body strength compared to DELOAD. Additionally, TRAD showed some slight psychological benefits as assessed by the readiness to train questionnaire over DELOAD. Conclusion In conclusion, our findings suggest that a 1-week deload period at the midpoint of a 9-week RT program appears to negatively influence measures of lower body muscle strength but has no effect on lower body hypertrophy, power or local muscular endurance.